Covariation of redox potential profiles and water table level in peatland sites representing different drainage regimes: implications for ecological modelling - Koskinen, Markku; Anttila, Jani; Vranová, Valerie; Holík, Ladislav; Roche, Kevin; Vorenhout, Michel; Pihlatie, Mari; Laiho, Raija (Copernicus Publications, 2025)
Reduction–oxidation (redox) reactions are ubiquitous in nature and are responsible for the energy acquisition of all organisms. Redox reactions are electron transfer reactions that necessarily involve two participants: one being oxidised (electron donor) and one being reduced (electron acceptor). The availability of terminal electron acceptors (TEAs) is a major determinant of the extent to which carbon in organic matter can be oxidised in an ecosystem. This is most important under waterlogged conditions, such as in peatlands, where the diffusion of O2, the most effective common TEA, into soil is blocked by water. Under these conditions, alternative TEAs can be used by microbiota to continue organic matter oxidation. Decomposition processes in soil can be characterised by its redox state, i.e. which TEA is responsible for organic matter oxidation at a given time. This can, in principle, be measured as a voltage between the soil solution and a known reference electrode, known as the redox potential. Current soil ecosystem models do not depict the use of alternative TEAs well. This limits their applicability for predicting soil carbon loss under different drainage regimes and, thus, their usefulness for assessing the best management practices for soil carbon preservation and water course protection. The most common determinant of the mode of decomposition presently used in ecosystem models is the water table level (WTL), which relies on the assumption that the redox state of a peatland ecosystem responds predictably to changes in the WTL. We conducted a 2-year redox monitoring experiment in a boreal mesotrophic peatland under three drainage regimes: undrained, short-term drainage, and long-term drainage. In addition, an ombrotrophic plot that had undergone long-term drainage was monitored. Snapshot assessments of the activity of three major metabolic enzymes – arginine deaminase, protease, and urease – were also undertaken at the mesotrophic plots as an indicator of differences in microbial activity between drainage regimes. We found that the WTL was a poor temporal predictor of redox potential but that (1) the position of major transition zones between oxic and anoxic states and (2) enzymatic activities within the peat profile were somewhat determined by the dominant WTL depth. In the undrained plots especially, redox potential values reflecting oxic or suboxic conditions were often found below the WTL, whereas anoxia was present above the WTL at the drained plots. Preceding redox potential was found to affect the activities of protease and urease but not arginine in all plots.
Keywords: redox; peatlands; drainage